(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
The Timurid period, spanning from the late 14th to the early 16th century, marked a golden era in Central Asian and Persian history. Under the leadership of Timur (Tamerlane) and his descendants, the Timurid Empire witnessed the flourishing of art, science, and architecture. One distinctive feature of Timurid architecture that continues to captivate historians and art enthusiasts alike is the exquisite use of tiles in the construction of historical monuments.